Do student nurses’ attitudes toward care of the dying vary between educational programmes and stage of study? - Grubb, Catherine Amy (2013)
Background Every year in the United Kingdom approximately half a million people use palliative care services, with most deaths occurring in hospital. The care that nurses provide can be influenced by their attitude. All patients, especially those at the end of life, require holistic care. Attitudes formed through undergraduate nurse training can influence the quality of nursing care provided to dying patients. Negative views of death and dying may have a detrimental effect on those receiving end of life care services. Aim The aim of this study was to investigate the relationship between palliative care education, experience in caring for people who are dying, and student nurses’ attitudes towards care of the dying. Methods A quantitative methodology was used to survey student nurses using a self-completion questionnaire. The Frommelt attitude toward care of the dying (FATCOD) scale was used to measure respondents’ attitude towards dying individuals and their families. Experience with caring for dying patients was measured by self-report. Hours of taught education was collected from course administrators. Findings A total of 567 completed questionnaires were received from 628 distributed. Student nurses who reported having cared for a dying patient had more positive attitudes towards end of life care then those without experience (difference in FATCOD score 5.2, 95% CI 3.85 to 6.6, p<0.001). Students who had not yet had any lectures on death and dying had a lower mean attitude score then those who had received the maximum of 15 hours (difference in FATCOD score 6.4, 95% CI 4.04 to 8.84, p<0.001). Conclusion Both education and experience with death and dying were associated with a more positive attitude towards care of the dying. These differences were small but statistically significant. The findings suggest that if more palliative care education is incorporated into undergraduate nursing curriculum, then increased knowledge and understanding may lead to better care delivered by nurses before and after qualification.